2013
DOI: 10.1177/1088868313490248
|View full text |Cite
|
Sign up to set email alerts
|

Resilience in Lesbian, Gay, and Bisexual Individuals

Abstract: To promote psychological health among lesbian, gay, and bisexual (LGB) individuals, more comprehensive research on resilience factors in LGB individuals is needed. This article presents a theoretical framework based on the existing literature, with an eye toward guiding future research in this area. Social support clearly serves as a resilience factor for LGB individuals, in part through its ability to lower reactivity to prejudice. Social support is particularly effective when it specifically supports people'… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
257
2
9

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 253 publications
(282 citation statements)
references
References 117 publications
14
257
2
9
Order By: Relevance
“…Due to their risk exposure, LGB tend to display a more weakening pattern than heterosexuals in variables like hope, self-esteem, emotional regulation, social isolation and substance abuse (Hatzenbuehler, 2009). As regards the mechanisms that seem to favor the resilience process in LGB, the literature highlights the coping strategies used, the perceived social support, the valuation of the LGB identity (Meyer, 2003), emotional openness and an optimistic perspective towards the future (Kwon, 2013). At the relational level, the importance of positive and non-conflicting relationships was also observed, as well as the perceived acceptance in the family and school contexts (D'Augelli, 2002;Ryan, Russell, Huebner, Diaz, & Sanchez, 2010;Saewyc, 2011;Ueno, 2005).…”
Section: Methodsmentioning
confidence: 99%
“…Due to their risk exposure, LGB tend to display a more weakening pattern than heterosexuals in variables like hope, self-esteem, emotional regulation, social isolation and substance abuse (Hatzenbuehler, 2009). As regards the mechanisms that seem to favor the resilience process in LGB, the literature highlights the coping strategies used, the perceived social support, the valuation of the LGB identity (Meyer, 2003), emotional openness and an optimistic perspective towards the future (Kwon, 2013). At the relational level, the importance of positive and non-conflicting relationships was also observed, as well as the perceived acceptance in the family and school contexts (D'Augelli, 2002;Ryan, Russell, Huebner, Diaz, & Sanchez, 2010;Saewyc, 2011;Ueno, 2005).…”
Section: Methodsmentioning
confidence: 99%
“…A more recently conducted study exploring hardiness among young adults also found support for the main effect and interaction models in the role of hardiness in reducing the impact of stressful life events on psychological distress (Beasley et al, 2003). Kwon (2013) has suggested that hardiness and adaptive coping behaviors may be particularly important resilience factors for lesbian, gay, and bisexual (LGB) individuals because these factors may reduce reactivity to prejudice and prepare LGB persons to cope with minority stress. Taken together, hardiness/adaptive coping may be an important asset that, like self-efficacy, plays compensatory and protective roles in reducing poor psychosocial outcomes among YBGBM.…”
Section: Hardiness and Adaptive Copingmentioning
confidence: 99%
“…While studies of youth of color have not shown peer or friend social support to be a significant resilience factor in compensatory or protective models (O'Donnell et al, 2004;Zimmerman et al, 2000), research conducted with LGB individuals suggests that peer support may be a critically important protective factor in managing minority stress related to sexual identity (Choi, Han, Paul & Ayala, 2011;Herrick, Stall, Goldhammer et al, 2013;Kwon, 2013;Riggle, Whitman, Olson, Rostosky & Strong, 2008). Moreover, several studies suggest that support received from various sources may play a critical role in promoting positive health outcomes among YBGBM.…”
Section: Social Supportmentioning
confidence: 99%
“…However, gender identity and sexual orientation remain discrete constructs and can result in different issues. For instance, transgender individuals who choose to undergo gender affirmation encounter unique social, physical, and psychological challenges that are not experienced by their gay, lesbian, and bisexual counterparts (Kwon, 2013;Pepper & Lorah, 2008). General attitudes toward transgender individuals are often much more hostile than those toward gay, lesbian, or bisexual individuals, and can therefore exert more several personal and professional consequences (Human Rights Campaign, 2009;Kwon, 2013;Ozturk, 2011).…”
Section: Why Are Trans Voices Unheard?mentioning
confidence: 99%